Right coronary artery originating from the left anterior descending artery, or double localized stemi with a twist: case report - Gábor Gergely; Zsolt István Szabó; Zsolt Körömi; Csaba Petrov (Cardiologia Hungarica)
In our case report, we describe an incidental finding of a congenital malformation of a coronary artery in a patient with acute coronary syndrome and we would like to present the importance of these findings. Coronary anomalies in an otherwise structurally normal heart are rare entities, yet their knowledge is necessary even for practicing cardiologists, especially those performing coronary interventions. In the single coronary artery cases – as the name suggests – the entire coronary artery system originates from a single common trunk. One of the more common variations occurs when the main trunk originates from the left Valsalva sinus and the right coronary artery originates from the proximal or medial section of the left anterior descending artery. In such anatomical conditions, choosing the planned interventional strategy is of great importance as a potentially larger myocardial area may be at risk during an acute coronary syndrome or in the event of an interventional complication.